O (des)conceito de Homem na leitura do espaço-tempo postulado na Geografia Humana : os enigmas de uma Geografia Humana sem homens - Dutra Júnior, Wagnervalter (2015)
This Doctoral Thesis, aim to reflect the conception of man inscribed in the reading of space-time postulated by human geography in the modern and iluminist context. It was initially developed the conception of man by the reading from the emancipatory space-temporal experience of modernity and universalization of exchange value, of the circularity of the capital space-time where social relations composes a geography expresses in Parisian passages, representing the fetishistic expansion of commercial domain as well as the expansion of distance processes of the ontological objectivity from the use value, with the production of space-time and man molded by the domain of value. The reading of modernity, underlying the universal process of exchange value, searches the intricacies of the experience of space-time that is structured from the sociability established by the capitalist system and the emancipatory project that the development of productive forces and production relations registered in the capital x work embodied contradiction. The progress and the emancipatory resizing of effective modern experience are evident, however, limits are imposed because of the control and domination that private property and exchange value exert in this experience backed by the abstraction of the political State and civil society. Emancipation acquires a meaning that ends up expressing a partial man, free in the field of political emancipation, as a citizen, but still unaware of the human emancipation. At this conjuncture the reason and progress eventually expand the alienating aspects that are set by social division of labor supported in the exchange value, and the praxis arises as mediator between political emancipation and human emancipation. Human geography, contextualized in its institutional bonds corroborates with the produced space-time to the capital by the production of work territories/abstract richness, to establish a reading of a man as externality spacetemporal, socially and spatially alienated .